Urban transport. Smart strategies to meet the requirements of tomorrow. - (:unkn) unknown (Deutscher Verkehrs-Verl., 2015)
Die Themen im Einzelnen: M. Svítek: Urban transport - a big challenge (S. 3-5); "Transport policy matters!" Interview with José Viega (S. 6-7); L. Schnieder / G. Tschare: Passenger information using a sign language avatar. Individual travel assistance for passengers with special needs in public transport (S. 8-10); W.-H. Arndt: New towns and transportation. Integrated urban and transportation planning for GHG emission reduction in the Young Cities project (S. 11-15); S. Flores: Providing local presence in a European network. International cooperation and knowledge exchange on e-mobility in the municipal and regional context (S. 16-17); P. Daude / W. Forderer: CIVITAS 2MOVE2 project. Putting sustainable mobility into practice in European cities (S. 18-21); I. Eekhoff: Sustainable mobility made in Germany. The German Partnership for Sustainable Mobility - a promising network for sustainable solutions (S. 22); A. Jung: Fewer cars, more mobility. Can carsharing work in China? (S. 26-29); G. Schmorl / M. Engelskirchen: MoveWindhoek - Sustainable urban transport in Namibia. Challenges and solutions for an African flagship project in urban transport development (p. 30-33); Lörrach banks on electric mobility (S. 34-36).
Keywords: Öffentlicher Verkehr; Verkehrsplanung; Stadtverkehr; Verkehrskonzept; Mobilität; ÖPNV; Stadtplanung; Umweltverträglichkeit; Nachhaltigkeit; Verkehrssteuerung; Logistik; Mobilitätsverhalten; Elektromobilität; Fahrgastinformation